c.1263+1G>A Is a Latent Hotspot for CYP27A1 Mutations in Chinese Patients With Cerebrotendinous Xanthomatosis - Jiang, Jingwen; Chen, Guang; Wu, Jingying; Luan, Xinghua; Zhou, Haiyan; Liu, Xiaoli; Zhu, Zeyu; Song, Xiaoxuan; Wang, Shige; Qian, Xiaohang; Du, Juanjuan; Huang, Xiaojun; et al. (Frontiers in Genetics, 2020)
Background: Cerebrotendinous xanthomatosis(CTX) is an autosomal recessive disorder of bile acid synthesis caused by mutations in the CYP27A1 gene. CTX is an underdiagnosed and potentially treatable disease, thus a detailed appreciation of the phenotypic spectrum and genetic characteristics are crucial for early diagnosis and treatment. Objectives and methods: Four CTX families with mutations in the CYP27A1 gene were enrolled in our study. We investigated the clinical characteristics and molecular genetic features of the probands with CTX. Genetic analysis was performed for detecting gene variants. Sanger sequencing and segregation analysis were conducted for haplotype analysis. Results: All the four probands were compound heterozygote for two CYP27A1 variants, including one mutation in c.1263+1G>A (intron 7) splice site, two novel likely pathogenic mutations(c.255+1G>T and c.1561dupA) and three pathogenic mutations including c.379C>T, c.1263+1G>A and c.1537C>T previously reported. All of the subjects presented with spastic paraparesis. The other common clinical features included ataxia, childhood-onset diarrhea, cataracts, intellectual disability, tendinous xanthomas and dentate nuclei signal alterations at MRI. Conclusions: Two novel likely pathogenic mutations(c.255+1G>T and c.1561dupA) were reported in our study. The 1263+1G>A mutation was commonly seen in Chinese reported case series (7/25, 28%) and could be a latent hotspot for Chinese CTX mutations. Our study expanded the mutation spectrum of CYP27A1 gene and provide an insightful view of the phenotypic spectrum and genetic characteristics to help early diagnosis and treatment with to improve neurologic dysfunction.